(untitled) (Educational Dimension, 2020)
The article deals with the problem of the development of intercultural competence, which is one of the key competences in foreign language education. The focus lies on examining the opportunities available to use the topic of German Trails in Ukraine as a material for developing intercultural competence. The theoretical foundations on which the research was conducted are analyzed: the essence of intercultural communication, the conditions of its smooth flow; the essence of intercultural competence, its constituents and the relations between them; the role of country studies (both the country of the target language and its own history) in the acquisition of background knowledge, the ability to compare cultures, to tolerate differences between them, and furthermore. Considering that the development of intercultural competence at a level that would ensure the effective implementation of intercultural communication is primarily due to the presence, in addition to language acquisition, of intercultural knowledge, perceptions of the rules of communicative behavior and the positive disposition of learners, an important element is the approaching of the target culture, the removal of prejudices about the „alien“. This can be achieved through the inclusion in the educational process of materials from the immediate environment of learners. For exemple, the theme „Traces of the Germans in Ukraine“ is used, in which work, on the one hand, reveals facts of the history of the Germans and Germany in the European format, and on the other, the facts of the history of their own country, the history of their immediate surroundings, at the expense of which the story of „alien“ is transferred to the personal sphere. Among the possible forms of work on the topic focuses on three: work with texts containing information, the history of the Germans as a motivation for communication, the implementation of an interdisciplinary approach to training of project activities.